sin (90° - 2°) - cos (180° - 2°) + tg (180° - 2°) - ctg (270° + 2°) =
sin (90°) * cos (2°) - cos (90°) * sin (2°) -
cos (180°) * cos (2°) - sin (180°) * sin (2°) +
( (tg (180°) - tg (2°) ) / (1 + (tg (180°) * tg (2°) ) -
(ctg (270°) * ctg (2°) - 1) / (ctg (270°) + ctg (2°) ) =
1 * cos (2°) - 0 -
(- 1) * cos (2°) - 0 +
(0 - tg (2°)) / (1 + 0) -
(0 - 1)/ (0 + ctg (2°)) =
cos (2°) + cos (2°) - tg (2°) + 1/ ctg (2°) =
cos (2°) + cos (2°) - tg (2°) + tg (2°) =
2 cos (2°).
Ответ: 2 cos (2°).
Автор:
edgar40Добавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть